Tradisi Jamaahan Empat Puluh Hari Kajian Living Hadis Di Desa Jatipurus Kecamatan Poncowarno Kabupaten Kebumen - Nur Wakhid (Jurnal Penelitian Agama, 2021)
The tradition of forty-five-day congregation was developed by the creativity of religious figures in Jatipurus Village as a persuasive approach in order to promote the sharia of congregational prayer within the society. To support the arguments of that tradition, they combined the hadith encouraging forty-day congregational prayer with the hadith commanding to increase worship during the sacred months (glorified months). The practice of this congregational prayer was established in one of the sacred months, it was arranged from the 20th of Dzulhijjah to the 30th of Muharram. There was a strong correlation and combination between the charismatic religious figures and the hadith. It was proven by the enthusiastic involvement of Jatipurus society during the forty-five-day congregation that was arranged annually; as a sequence, it was recognized as a tradition. The fundamental part of that tradition was tasyakuran in which it was engaged in the activities of tahlil, religious talks, prayers, and then it was ended by having meals together. That tradition was investigated and analyzed by implementing Karl Mannheim’s theory on the sociology of knowledge. The concentration of this research was related to three aspects of meaning. The first, the objective meaning: it showed that the people of Jatipurus believed that the tradition of forty-five-day congregation was a legacy of their predecessors. The second, the expression meaning: the society who joined the congregation believed that by consistently performing the forty-five-day congregation could save them from two things: the torment of the fire and hypocrisy. Finally, the third, the documentary meaning: they did not realize the implied meaning of the tradition, in which the implementation of the forty-five-day congregation was an expression of a religious culture.